Effect of change in the CG CAHPS survey instrument recall period on patient experience scores on healthcare utilization - Kimberley Marshall-Aiyelawo; Richard Bannick; Sharon Beamer; Melissa Gliner; Terry McDavid; Daniel Muraida; Janice Ellison; Beatrice Abiero; Alan Roshwalb; Mark Andrews (The Beryl Institute, 2019)
Standardized patient experience survey instruments play an important role in informing healthcare quality and process improvement. However, any changes in standardized instruments can impact the interpretation, trending, and analysis of patient reported data. This study investigates how the change in Clinician and Group Consumer Assessment of Healthcare Providers and Systems (CG CAHPS) survey recall period, from 12- to 6-months, can impact the accuracy and quality of patient experience data. This study used primary survey data on patient experience collected in 2016. Analyses included tests of proportion and t-tests for a comparison of: 1) experience ratings, and 2) administrative data to corroborate how accurately respondents report the number of visits received within the recall period. The findings indicated that respondents, on average, underestimated their usage of care based on a 12-month recall period, apart from those who reported just one visit. A shorter 6-month recall period resulted in higher accuracy in reporting the number of actual visits that occurred. Furthermore, experiential measures showed consistently higher scores across measures for Provider Communications, Staff Communications, Timely Access to Care, and Care Coordination for a 6-month recall period compared to a 12-month period. This study showed that it would be difficult to compare CG CAHPS Version 2.0 to Version 3.0 due to recall differences in experiential measures. Given that shorter recall periods tend to be associated with higher CG CAHPS ratings, healthcare stakeholders should consider bias introduced by changes of recall periods in survey instruments. Experience Framework This article is associated with the Policy & Measurement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Policy%20%26%20Measurement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.